Estimating the Causal Relationship between Renewable Energy Consumption, Tourism and Economic Growth: Evidence from Algeria - Benchouk, Wahiba (Finance and Business Economies Review, 2021)
The main objective of this study is to investigate the causal relationship between renewable energy consumption, tourism and economic growth in Algeria spanning the period 1990-2018. In order to examine the long-run relationship, the ARDL bound testing approach for cointegration is applied. The study further applied Toda-Yamamoto causality test to reveal the direction of causalities. The empirical results reveal the existence of a long-run relationship across the variables. However, Toda-Yamamoto causality findings support the presence of the unidirectional causal relationship running from tourism to renewable energy consumption. Algeria must implement sustainable tourism practices that could mainly cause an increase in renewable energy consumption.